Rationale for use Dexketoprophenum in the early postoperative period analgesia in oncosurgery. - Dmytriiev, D. V.; Dmitrieva, E. Yu.; Semenenko, A. I.; Sursaev, Yu. E.; Bilash, M. O. (Pain medicine, 2016)
The studies were conducted in 64 patients (16,4 ± 1,2 years) operated for retroperitoneal tumors (44 patients, 69 %), ovarian cancer (20 patients, 31 %). The studies were conducted in two groups of patients (n = 64), 10 mg morphine analgesia (34 patients) as standard, and Dexketoprophenum (30 patients) according to the scheme: 1st injection of 50 mg dose intramuscularly 40 minutes before surgery, 2nd injection of the same dose (50 mg im) after 8 hours from the 1st injection and 3rd one – of the same dose (50 mg im) after 8 hours of the 2nd injection. Daily dose of drug was less than 150 mg/day. The use of Dexketoprophenum can significantly reduce the need for opioids, and their combination can restore the analgesic potential of the latter. Various mechanisms of action of these drugs allows to assign them in combination and in small doses to achieve significant analgesic effect. Prescribing Dexketoprophenum can significantly reduce abdominal hypertension manifestations and improve blood flow in the major vessels of the abdominal cavity, according to ultrasound investigation.